Riding the Roller Coaster : Fiscal Policies of Nonrenewable Resource Exporters in Latin America and the Caribbean - Lopez Murphy, Pablo (IMF Working Papers; Working Paper ;, 2010)
This paper analyzes recent fiscal policies of nonrenewable resource exporting countries in Latin America and the Caribbean in the context of sharp swings in resource prices. Fiscal policies were predominantly procyclical during the boom period 2003-08 but to significantly differing degrees within the sample. Countries that pursued more conservative fiscal policies during the boom were then able to implement countercyclical fiscal policies during the downturn; moreover, they reduced or maintained their fiscal vulnerability to resource shocks, while their long-term fiscal sustainability positions improved or were broadly unchanged. However, these dimensions of fiscal policy did not seem to be linked to fiscal rules or resource funds, as countries with such institutions displayed a broad range of fiscal responses to the recent cycle.